An Analysis of Reinfection Pneumonia Model with Carrier State - et. al., Naga soundarya lakshmi V.S.V , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A reinfection model with Carrier state for pneumonia was formulated. The boundedness and positiveness of the state variables were verified. The local and global stability of the model was established. By the equilibrium analysis the optimal values of Susceptible, Infectious, Carrier and Recovery were found. Through the numerical simulations, the flow of S,I,C,R and the flow of variables for different set of parameters were studied.